Isolation, Characterization And Biological Evaluation Of Iron Chelator From Triticum Aestivum (Wheat Grass) - P. R. TIRGAR; B. L. THUMBER; T. R. DESAI (International Journal of Pharma and Bio Sciences, 2011)
Triticum aestivum, is a one of the important species of wheatgrass, a cereal grass of Gramineae (Poaceae) family. Proponents of wheatgrass make many claims for its health properties, ranging from promotion of general well-being to cancer prevention and heavy metal detoxification. These claims have not been satisfactorily substantiated in scientific literature. Iron overload is one of the major causes of morbidity in all patients with severe forms of thalassemia and other iron overloaded disorders. Our previous study showed beneficial effects of methanol extracts in iron overloaded animals. Thus present study was planned to isolate and characterize iron chelating compound from methanol extract of wheatgrass. This isolated compound was subjected to determination of iron chelating activity in iron dextran induced acute iron overload animals. At the end of our study, we are able to characterize compound using LCMS and IR spectroscopy. Result inference is that isolated compound belonging to phenolic group and possesses in-vitro iron chelating activity. The isolated compound also possesses phenolic content which is confirmed using FC method. We have made the unexpected observation that this isolated compound from T. aestivum strikingly increase iron in urine in iron loaded animals. The chelating power or efficacy of the compound was found to be 34.5% to that of desferoxamine, a standard iron chelator used to reduce iron overload in thalassemia. In conclusion, our data suggest that isolated compound from Triticum aestivum possess iron chelator compound which is belonging to phenolic group.